Flavonoids as Scavengers of Nitric Oxide Radical - Vanacker, S.A.B.E.; Tromp, M.N.J.L.; Haenen, G.R.M.M.; Vandervijgh, W.J.F.; Bast, A. (Biochemical and biophysical research communications, 1995)
Flavonoids are a group of naturally occurring compounds used, e.g., in the treatment of vascular endothelial damage. They are known to be excellent scavengers of oxygen free radicals. Since the nitric oxide radical ( . NO) probably plays a role in this pathology, the . NO scavenging capacity of the flavonoids was determined. It was found that the flavonoids are very potent . NO scavengers. The anthocyanidins were found to be more effective scavengers than the hydroxyethylrutosides, which correlated with their therapeutic activity. The values of their scavenging rate constants are only 30 times less active than the very potent endogenous . NO scavenger haemoglobin. It is speculated that . NO scavenging plays a role in the therapeutic effect of the flavonoids.